Experimental studies on particle emissions from cruising ship, their characteristic properties, transformation and atmospheric lifetime in the marine boundary layer - Petzold, A.; Hasselbach, J.; Lauer, P.; Baumann, R.; Franke, K.; Gurk, C.; Schlager, H.; Weingartner, E. (Atmospheric chemistry and physics, 2008)
Particle emissions from ship engines and their atmospheric transformation in the marine boundary layer (MBL) were investigated in engine test bed studies and in airborne measurements of expanding ship plumes. During the test rig studies, detailed aerosol microphysical and chemical properties were measured in the exhaust gas of a serial MAN B&W seven-cylinder four-stroke marine diesel engine under various load conditions. The emission studies were complemented by airborne aerosol transformation studies in the plume of a large container ship in the English Channel using the DLR aircraft Falcon 20 E-5. Observations from emission studies and plume studies combined with a Gaussian plume dispersion model yield a consistent picture of particle transformation processes from emission to atmospheric processing during plume expansion. Particulate matter emission indices obtained from plume measurements are 8.8±1.0×1015(kg fuel)−1 by number for non-volatile particles and 174±43 mg (kg fuel)−1 by mass for Black Carbon (BC). Values determined for test rig conditions between 85 and 110% engine load are of similar magnitude. For the total particle number including volatile compounds no emission index can be derived since the volatile aerosol fraction is subject to rapid transformation processes in the plume. Ship exhaust particles occur in the size range Dp<0.3 μm, showing a bi-modal structure. The combustion particle mode is centred at modal diameters of 0.05 μm for raw emissions to 0.10 μm at a plume age of 1 h. The smaller-sized volatile particle mode is centred at Dp≤0.02 μm. From the decay of ship exhaust particle number concentrations in an expanding plume, a maximum plume life time of approx. 24 h is estimated for a well-mixed marine boundary layer.